Abstracts of Philippine researches in home economics, 1923-1978 - Domingo, Generosa T.; Picache, Ursula G. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1981)
The study aims to compile into a single volume abstracts of all available bachelor's and master's theses, special problems, seminar papers and doctoral dissertations in home economics which have been completed and submitted to degree-granting institutions of the United States and the Philippines for the period 1923-1978.
The objectives of the study are to: 1) obtain information regarding the different studies related to home economics done in private and government educational institutions; 2) determine the different areas of home economics that have been well explored, as well as areas that should be studied more; 3) define and establish the trend of studies in the various areas of home economics; 4) determine the practical value and significance of these studies in the light of technological and social change; 5) understand how the different Philippine government agencies and educational institutions complement each other in the realization of these objectives; and 6) know the extent to which the awareness of these findings aids the researchers in the planning programs and in advising students in their choice of research topics.
Three methods were used to gather information for the study, namely: 1) the use of mailed questionnaires to home economics graduates; 2) an actual survey of libraries of educational institutions both private and government and some government agencies; and 3) compiled published and unpublished sources of theses abstracts in professional journals and scientific reports.
The study includes 406 researches of graduate and undergraduate students from private and government educational institutions in the four areas of home economics, namely: 1) Food Science and Nutrition, including Institution Management and Hotel and Restaurant Administration; 2) Clothing, Textiles, and Related Arts; 3) Family Life and Child Development; and 4) Home Economics Education.
Indexes: leaves [448]-496
Mimeographed.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: Home economics -- Research -- Abstracts